2001
DOI: 10.37236/1574
|View full text |Cite
|
Sign up to set email alerts
|

An Extension of a Criterion for Unimodality

Abstract: We prove that if $P(x)$ is a polynomial with nonnegative nondecreasing coefficients and $n$ is a positive integer, then $P(x+n)$ is unimodal. Applications and open problems are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…The objective of this note is to give a proof of Moll's conjecture on the minimum value of a sequence involving the coefficients of the Boros-Moll polynomials which arise in the evaluation of the following quartic integral, see, [1][2][3][4][5][6]11]. It has been shown that for any a > −1 and any nonnegative integer m, ∞ 0 1 (x 4 + 2ax 2 + 1) m+1 dx = π 2 m+3/2 (a + 1) m+1/2 P m (a), where…”
Section: Introductionmentioning
confidence: 99%
“…The objective of this note is to give a proof of Moll's conjecture on the minimum value of a sequence involving the coefficients of the Boros-Moll polynomials which arise in the evaluation of the following quartic integral, see, [1][2][3][4][5][6]11]. It has been shown that for any a > −1 and any nonnegative integer m, ∞ 0 1 (x 4 + 2ax 2 + 1) m+1 dx = π 2 m+3/2 (a + 1) m+1/2 P m (a), where…”
Section: Introductionmentioning
confidence: 99%
“…Now let j ≥ m. Then (d+1)(j +1) ≥ (d+1)(m+1) ≥ m+1 by (1). Every term in the sum ( 2) is therefore non-positive, and thus b j+1 ≤ b j .…”
Section: Conjecture 11 ([1]mentioning
confidence: 99%
“…Let P (x) be nonnegative and non-decreasing. It is shown that P (x + 1) is unimodal in [2] and more generally, that P (x + n) is unimodal when n is a positive integer in [1]. Further, the following is conjectured.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…that satisfies P m (x) = A(x + 1). The criterion was extended in [1] to include the shifts A(x+ j) and in [32] for arbitrary shifts. The original proof of the unimodality of P m (a) can be found in [7].…”
Section: Unimodality and Log-concavitymentioning
confidence: 99%